EZH2-regulated PARP-1 Expression is a Likely Mechanism for the Chemoresistance of Gliomas to Temozolomide - Liang, Qiang; Wang, Bing; Zhang, Chenran; Song, Chaoli; Wang, Junyu; Sun, Wei; Jiang, Lei; Lin, Jing (Current Cancer Drug Targets, 2024)
Background: Chemoresistance in gliomas accounts for the major cause of tumor progress and recurrence during comprehensive treatment with alkylating agents including temozolomide (TMZ). The oncogenic role of Enhancer of zeste homolog 2 (EZH2) has been identified in many solid malignancies including gliomas, though the accurate effect of EZH2 on chemotherapy resistance of gliomas has been elusive. Objective: To elucidate the role of EHZ2 on TMZ resistance of gliomas and the molecular mechanisms. Methods: Immunohistochemistry (IHC) and Reverse transcription-quantitative (RT-q) PCR, and western blot assay were performed for expressional analysis. Cell Counting Kit-8 (CCK-8) assay was applied to determine the TMZ sensitivity. EZH2-silencing lentivirus was generated for mechanic study. Results: EZH2 was overexpressed in gliomas both at the transcriptional and protein levels. EZH2 level in glioma cell lines was positively correlated with resistance to TMZ, represented by the 50% inhibition rate (IC50). Moreover, there was increased TMZ sensitivity in EZH2-inhibited glioma cells than in the control cells. Furthermore, we determined that PARP1 was a common molecule among the downregulated DNA repair proteins in both U251 and U87 glioma cell lines after EZH2 inhibition. Specifically, we observed a spontaneous increase of PARP1 expression with TMZ treatment and interestingly, the increase of PARP1 could be also reduced by EZH2 inhibition in the glioma cells. Finally, combined treatment with lentivirus-induced EZH2 inhibition and a PARP1 inhibitor dramatically enhanced TMZ cytotoxicity compared with either one alone. Conclusion: EZH2-PARP-1 signaling axis is possibly responsible for the chemoresistance of gliomas to TMZ. Simultaneously inhibiting these two genes may improve the outcome of TMZ chemotherapy.
Keywords: chemoresistance